THE DEVELOPMENT OF LAKTONA FOR IMPROVING LEARNING OUTCOMES OF NATIONAL RESILENCE OF 3RD GRADE OF PRIMARY SCHOOL STUDENTS - Santoso, Ikha Budi (Universitas Negeri Semarang, 2018)
The objectives of this research were to develop the Laktona learning media, to examine the effectiveness and expedience of Laktona learning media to improve the learning outcomes of National Resilience of 3rd grade students of SDN Pakintelan 03 Kota Semarang. The research method was Research and Development (R&D). The result of this research indicated that the learning media named Laktona can improved the learning outcomes, it can be seen with increasing the rate of learning outcomes of posttest used the Laktona media about 0,592 (medium level). The validation results of media and material expert indicated that the Laktona media was suitable applied in the National Resilience Learning with average score about 3,61 of 4 by media expert and 3,89 of 4 by material expert. The result of teacher responds showed that average score 4 of 4, it is worthed to applied in elementary students. Laktona learning media was applied effectively, this result was supported by the average difference of students' understanding through the t test was 11,834 with significance value of 0,000. So that, Ha was accepted because the significance was < 0,05. It means there is difference of learning outcomes of pretest and posttest. The conclusion of this research showed that the learning media named Laktona can improved the learning outcomes of National Resilience about Norm. Keywords: LAKTONA; Learning outcomes; National Resilience (PKn).